Recurrent Partial Hydatidiform Mole: A Case Report of Seven Consecutive Molar Pregnancies - Salima S; Wibowo MH; Dewayani BM; Nisa AS; Alkaff FF (Dove Medical Press, 2023)
Siti Salima,1 Mulyohadi Hadi Wibowo,1 Birgitta M Dewayani,2 Aisyah Shofiatun Nisa,1 Firas Farisi Alkaff3,4 1Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Padjadjaran-Dr. Hasan Sadikin Hospital, Bandung, Indonesia; 2Department of Pathology of Anatomy, Faculty of Medicine, Universitas Padjadjaran-Dr. Hasan Sadikin Hospital, Bandung, Indonesia; 3Division of Pharmacology and Therapy, Department of Anatomy, Histology, and Pharmacology, Faculty of Medicine Universitas Airlangga, Surabaya, Indonesia; 4Division of Nephrology, Department of Internal Medicine, University Medical Center Groningen, Groningen, the NetherlandsCorrespondence: Siti Salima, Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Padjadjaran-Dr. Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, 40161, Indonesia, Tel +62811223830, Email s.salima@unpad.ac.id Firas Farisi Alkaff, Division of Pharmacology and Therapy, Department of Anatomy, Histology, and Pharmacology, Faculty of Medicine Universitas Airlangga, Surabaya, Indonesia, Tel +6281330101993, Email f.f.alkaff@umcg.nl; firasfarisialkaff@fk.unair.ac.idAbstract: Hydatidiform mole (HM) is an aberrant pregnancy characterized by atypical trophoblastic hyperplasia, hydropic chorionic villi, and deprived fetal development. There are two types of HM, ie, complete (CHM) and partial (PHM). Both CHM and PHM can recur; however, the recurrence of PHM is very scarce compared to CHM. In this report, we present a case of a 33-year-old woman with recurrent PHM for 7 times without any normal pregnancy in-between. PHM was determined by histology examination. The patient underwent suction curettage and was followed up with serial β-hCG levels. Recurrent PHM, although rare, is associated with an increased incidence of malignancy. A series of clinical and β-hCG evaluation should be warranted because of the possibility of gestational trophoblastic neoplasia development.Keywords: hydatidiform mole, pregnancy, partial hydatidiform mole, case report